Estudio de factibilidad para el desarrollo de un sistema de incidencia para soporte a usuarios del Gobierno Autónomo Descentralizado del cantón Babahoyo - Hipo Auquilla, Luis Fernando (2020)
The capital of the province of Los Ríos (Babahoyo) has its municipality, which is headed by Dr. Carlos German, current mayor of this city, all the departments of this GAD have computer equipment, in most cases they are teams with high performance to be able to serve citizens effectively. In summary, this case study is to determine if it is feasible to create an incidence system to support users of the Babahoyo Canton Autonomous Decentralized Government, said system will consist of an assignment of shifts to be able to be attended according to the order that said request has been made. , within the system department there is a support manager who has two people under his command, therefore when the officials call to report a problem they come in a disorderly way and without keeping track of what the problem was in the team, It should be noted that all the calls received are directly to the telephone to the head of the ICT department, with this system it is intended to attend to the problems in an orderly manner, assigning a shift and being able to solve it with more ease.